PARENT’S, TEACHER’S AND STUDENT’S PERCEPTIONS OF CHILDHOOD OBESITY IN THE MIDDLE EAST - Stott, Kelly; Marks, Ray; Allegrante, John P. (European Scientific Journal, ESJ, 2014)
The problem of overweight and obese children now constitutes a global epidemic, with high prevalence rates now being reported in many transitional societies. Half of the adults in the United Arab Emirates—one of the wealthiest advanced economies in the world—are overweight or obese and school-age children have experienced a marked increase in BMI. UAE children are 1.8 times more obese than those in the United States and, by age 18, obesity is approximately three times greater among UAE males than those in other countries. This project sought to identify the barriers that prevent UAE children from engaging in physical activity and healthy diets. We conducted face-to-face interviews with 57 participants living in the greater Ras Al Khaimah area of the UAE, along with observations and field notes, regarding perceptions about childhood overweight and obesity. Interview data were analyzed using qualitative and thematic methods. Physical inactivity and consumption of fast food and sugared beverages are perceived to contribute to the increase in obesity among UAE children. Social, cultural, and environmental barriers contribute to prevention of childhood obesity in RAK. These include: climate, gender bias, cultural attire, availability and accessibility of resources, technology, and lack of role models. Respondents recognize the problem of childhood obesity in their community and are eager to take part in promoting health awareness and other initiatives that address barriers and have the potential to help school-age children make healthy lifestyle choices. Teachers, parents, and students in the UAE recognize that being overweight or obese is a serious problem and acknowledge the need for changes in lifestyle in order to prevent the epidemic from continuing to rise. The UAE experience can help us to understand how overweight and obesity influence the health status of children in this and other transitional societies.